Plate tectonics in the classification of personality disorder: shifting to a dimensional model - Widiger, Thomas A; Trull, Timothy J (The American psychologist, 2007)
The diagnostic categories of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders were developed in the spirit of a traditional medical model that considers mental disorders to be qualitatively distinct conditions (see, e.g., American Psychiatric Association, 2000). Work is now beginning on the fifth edition of this influential diagnostic manual. It is perhaps time to consider a fundamental shift in how psychopathology is conceptualized and diagnosed. More specifically, it may be time to consider a shift to a dimensional classification of personality disorder that would help address the failures of the existing diagnostic categories as well as contribute to an integration of the psychiatric diagnostic manual with psychology's research on general personality structure.